PENGEMBANGAN MEDIA PEMBELAJARAN SNAKESEDU BOARD UNTUK MENGENALKAN ANGKA 1-10 DALAM BAHASA INGGRIS PADA ANAK USIA 5-6 TAHUN - Robi'atul Mudawamah; Dhian Gowinda Luh Safitri; Melia Dwi Widayanti; Fatiha Khoirotunnisa Elfahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The introduction of numbers and foreign languages from an early age is an important aspect of children's cognitive development. However, in kindergarten learning practices, the introduction of numbers 1–10 in English is often carried out through lecture and memorization methods without the support of engaging learning media. This condition makes children less motivated, easily bored, and find it difficult to understand the relationship between number symbols and their pronunciation in English. Therefore, innovative and enjoyable learning media are needed, in line with the characteristics of early childhood learning which tends to occur through play. This study aims to develop the SnakesEdu Board learning media to introduce numbers 1–10 in English to children aged 5–6 years. The research used the Research and Development (R&D) method with the ADDIE development model consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were nine children from TK Islam Al-Fatah Nginden Surabaya. The results showed that the SnakesEdu Board media is valid, practical, and effective in improving children's ability to recognize numbers 1–10 in English.